Waja : Sanksi Adat dalam Sistem Perkawinan di Desa Naru Kecamatan Bajawa Kabupaten Ngada Nusa Tenggara Timur - Mbapa, Anastasia Aprilia Mopo; Wiasti, Ni Made; Aliffiati, Aliffiati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Marriage is a life partnership that unites a man and a woman. Waja in the traditional community of Naru Village is known as customary sanctions which regulate matters relating to problems that occur in the marriage system. The aim of this research is to find out thoroughly about waja as a customary sanction in the marriage system in Naru Village, Bajawa District, Ngada Regency, East Nusa Tenggara. This study uses a qualitative method. Data collection techniques are observation, interviews and literature study.The results of this research explain that although there are many types of marriage believed by the people of Naru Village to have been passed down by their ancestors which are still maintained and carried out today, they are di’i sa’o and pasa. The people of Naru Village, in choosing their future life partner, follow the provisions and are not careless in their choice. This is to avoid the possibility of errors occurring in the future. Apart from marriages that are carried out through a good and correct process, there are also marriages that are not properly carried out according to custom. There are several terms for fines that must be paid in the traditional marriage process which will then continue the relationship to the stage of relationship restoration or be terminated. Violations that are feared to occur are violations committed if you do not know how to maintain boundaries, such as being impolite, having relationships without commitment, and forcing the opposite sex to do things that are not good. This will be subject to customary sanctions called waja or mena. Waja or mena is a form of punishment that has a big impact, especially on women, namely a form of self-reward for women, which is considered as payment for disrespectful behavior from men to women. Waja is a customary sanction that is used to sever legal relations according to custom, where women in this case are always the victims. It is hoped that the people of Naru Village will be more vigilant about young people’s interactions and can provide examples and advice so that they don’t do things that could eventually lead them to this stage of traditional waja sanctions.